2014
DOI: 10.1080/21507740.2014.939380
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Focal Points in the International Practice of Deep Brain Stimulation

Abstract: Deep brain stimulation (DBS) is a standard therapy for several movement disorders, and the list of further indications that are investigated is growing rapidly. We performed two surveys among DBS experts (n1D 113) and centers (n2D 135) to identify ethical focal points in the current global practice of DBS. The data indicate a mismatch between the patients' fears and the frequencies of the suspected side effects, a significant "satisfaction gap," signs of improvements of outcome, habituation effects in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…We found that the Internet and neurologists played a key role in referring patients and served as main sources of information for patients. Christen et al report comparable findings in which private practice neurologists were the decisive "entry point" to DBS; additionally, up to 53.1% of patients used the Internet as their source of information [26]. The public uses the Internet to engage in social media interactions.…”
Section: Points Of Entry and Information Regarding Dbsmentioning
confidence: 94%
See 2 more Smart Citations
“…We found that the Internet and neurologists played a key role in referring patients and served as main sources of information for patients. Christen et al report comparable findings in which private practice neurologists were the decisive "entry point" to DBS; additionally, up to 53.1% of patients used the Internet as their source of information [26]. The public uses the Internet to engage in social media interactions.…”
Section: Points Of Entry and Information Regarding Dbsmentioning
confidence: 94%
“…Another important concern in the neuroethical literature is that of personality changes. Christen et al [26] found that approximately 10% of their sample reported fear of personality changes. We found a similar percentage of patients reporting that fear, specifically prior to surgery.…”
Section: Patients Ethical Concerns With Dbsmentioning
confidence: 98%
See 1 more Smart Citation
“…At the same time, we see a trend of expanding the use of DBS for conditions that are not particularly well understood pathophysiologically, particularly in psychiatry, in underpowered clinical trials or even single cases. This trend needs to be monitored and critically examined, as this research often does not satisfy established scientific standards of incremental clinical research (Bittlinger 2017;Christen et al 2014). Noninvasive forms of neurostimulation such as transcranial direct current stimulation (tDCS), transcranial magnetic stimulation (TMS), and focused ultrasound (fUS) are likely to be used more broadly.…”
Section: Rapid Technological Changementioning
confidence: 99%
“…The results of this analysis are then reflected by referring to issues that dominated the DBS literature. Beside others, we are interested in how some topics that have been identified as ethical focal points in the international practice of DBS (Christen et al, 2014 ) are represented in this quantitative approach. In this way we explore the potential of such quantitative approaches for identifying subject matters that are of relevance from a bioethical perspective.…”
Section: Introductionmentioning
confidence: 99%